(untitled) - Pennypacker, Sara; 1951-; Tanaka, Yoko (New York, 2009)
When the ruler of China declares a "Sparrow War" against the birds that are eating the farmers' crops, little Ming-Li makes it her mission to save the unwanted birds from certain destruction.
Keywords: China; Fiction; Country life; Fiction; Pest control; Fiction; Sparrows; China; Fiction; History; 1949-1976